The Secondary Development and Application of the Improved Nishihara Creep Model in Soft Rock Tunnels - Xianghui Deng; Junxin Shi; Xiaolin Li; Rui Wang; Jinzeng Zhang; Xin Yang (Buildings, 2023)
Given the complexity and diversity of rock formations, existing constitutive models struggle to accurately portray their mechanical properties, leading to substantial discrepancies between numerical simulation outcomes and reality. This inadequacy fails to meet the demands of numerical analysis in practical engineering. This study first analyzes the physical and mechanical properties of thin-layered carbonaceous phyllite. Subsequently, an improved Nishihara rheological constitutive model is established based on these analyses. Utilizing the secondary development function offered by FLAC3D, the proposed model is further developed. The program’s correctness and reliability are confirmed through a numerical simulation using the triaxial creep test from existing research. Finally, the established constitutive model is applied in the numerical simulation of an actual soft rock tunnel engineering, obtaining results compared to real monitoring data. The results demonstrate that the improved Nishihara model is more effective at describing the creep deformation characteristics of soft rock. Moreover, the findings from this study can serve as a theoretical reference for predicting deformation in soft rock tunnel engineering.